The attic child : a novel - Jaye, Lola (William Morrow, an imprint of HarperCollins Publishers, 2022)
Two children trapped in the same attic, almost a century apart, bound by a shared secret. Early 1900s London: Taken from his homeland, twelve-year-old Celestine spends most of the time locked away in the attic of a large house by the sea. The only time Celestine isn't bound by confines of the small space is when he is acting as an unpaid servant to English explorer Sir Richard Babbington, As the years pass, he desperately clings on to memories of his family in Africa, even as he struggles to remember his mother's face, and sometimes his real name ... 1974: Lowra, a young orphan girl born into wealth and privilege whose fortunes have now changed, finds herself trapped in the same attic. Searching for a ray of light in the darkness of the attic, Lowra finds under the floorboards an old-fashioned pen, a porcelain doll, a beaded necklace, and a message carved on the wall, written in an unidentifiable language. Providing comfort for her when all hope is lost, these clues will lead her to uncover the secrets of the attic.